A curative approach for psoriasis vulgaris - VENNILA SUBRAMANAIAM; DR P. CHITRA (International Journal of Pharma and Bio Sciences, 2017)
Psoriasis vulgaris is a chronic, inflammatory disorder with multiple pathways. It is a skin mediated diseases due to the epidermal keratinoctyes, dermal vascular cells which includes activated antigen presenting cells. Interaction with the activated T cells with monocytes with Th17/IL-23 causes chronic inflammation. IL-17A induces expression of the keratinocyte chemokine CCR6. Trafficking of activated Th17 cells, but not of Th1 or Th2 cells, to psoriatic skin has been associated with CCR6 expression. Structure of the protein CCR6 was modeled using Modeller 9.17. Phytochemical compounds, beneficial effects on the plant host exhibit a series of biological properties that influence the human in a health-promoting manner. Due to their natural origin and low side effects it eliminates the causes and effects of psoriasis. Molecular docking studies were undergone using Auto Dock 4.2 and Docking Server.